Developing The E-Module of The Cidayu (Chinese, Dayak, and Malay) Community’s Local Wisdom Using Fliphtml5 Software - Marhayani, Dina Anika; Kariadi, Dodik; Setyowati, Rini; Mertika, Mertika; Cinda H, Evinna; Suprapto, Wasis; Wulandari, Fajar (LPPM Universitas Pendidikan Mandalika, 2025)
This study aims to develop the E-Module of the Cidayu (Chinese, Dayak, and Malay) community’s local wisdom using Fliphtml5 Software as a learning resource that incorporates cultural insights for students engaged in the foundational concepts of social studies. This study employed the research and development (R&D) method with the ADDIE model, which encompasses five stages: Analysis, Design, Development, Implementation, and Evaluation. The subjects of the study were 93 PGSD students in the 4th semester of ISBI Singkawang. The research instruments were questionnaire sheets, media and material expert validation sheets, and learning outcome questions. The data analysis techniques used in this study were qualitative and quantitative data analysis techniques. The research findings showed that the e-module was considered valid with an average value of 77.5% for media experts and 76.5 for material experts. The e-module also received a positive response from ISBI Singkawang PGSD students as seen from the results of the questionnaire responses seen from the appearance aspect getting a score of 75.8%, the ease of use aspect getting a score of 80%, and the usability aspect getting a score of 73.6%, resulting in an average score of 76.5 effectively empowering students to recognize, understand, respond, and engage with the local wisdom of CIDAYU. This study produced a T-count value of 8.236, exceeding the t-table threshold of 1.990. Therefore, it can be concluded that this electronic module can function as an independent learning resource that can be accessed for individual learning, so that it can improve students' learning achievements in terms of learning outcomes.